The Effect of Claim Expense Ratio and Net Premium Growth on Liquidity Ratio in General Insurance Companies Listed on the Indonesia Stock Exchange (2017–2024) - Hanaya Michelle Herwinata; Salma Farah Faiza; Michael Kidastra Latayu; Aisyah Rizki Adinda; Valeria Lisa Savitri; Muhammad Fazli Rabbaani; Dewi Hanggraeni (Lembaga Pengembangan Kinerja Dosen, 2026)
This research intends to examine the impact of Claim Expense Ratio (CER) and Net Premium Growth (PGR) towards Liquidity Ratio (LIQ) of general insurance firms quoted at Indonesia Stock Exchange (IDX), incorporating Firm Size as a control variable. Using panel data from 5 general insurance companies with the largest market capitalization during 2017–2024 (40 observations), this study applies the Pooled Ordinary Least Squares (OLS) method. The F-test confirms the model is jointly significant (F = 3.461; p = 0.026), accompanied by an R² of 22.4%. Partially, only Firm Size proves to have a significant negative effect on the Liquidity Ratio (β = -0.054; p = 0.008), while CER (β = -0.068; p = 0.205) and PGR (β = -0.116; p = 0.332) are not statistically significant. The non-significance of CER and PGR is explained through the OJK regulatory framework that mandates the formation of technical reserves, rendering the effect of claims and premium growth on liquidity indirect. These findings contribute to the understanding that firm size characteristics are more dominant in determining liquidity levels than operational dynamics of claims and premiums in the Indonesian general insurance industry.